PRINSIP KEADILAN DALAM PENYELESAIAN SENGKETA TANAH UNTUK KEPENTINGAN PEMBANGUNAN - Ibrahim Ahmad (Universitas Negeri Gorontalo, 2010)
Limited land availability and the amount that is not balanced with the needs anddesires of human beings is so great trigger rand disputes. Land dispute is a case that always dominate the case in court Factors affecting the enforcement of law against land disputes among other laws and regulations that are not singkron either vertially or horizontally, law enforcement agencies who are not professionals and have no moral integrity, and attitude of society is less obedient to the regulations. Land disputes that occurred should be resolved comprehensively and with more emphasis terintegral principles of justice through litigation or non litigation path Keywords: principles ofjustice, Land Disputes, Interest, Development